Effect of generation number on properties of fluoroalkyl‐terminated hyperbranched polyurethane latexs and its films. Issue 40 (10th March 2020) - Xu, Wei; Wang, Wen; Hao, Lifen; Zhao, Weijia; Liu, Hongna; Wang, Xuechuan
Abstract: The 1–3 generations of hyperbranched polyesters (HBPE‐1/2/3) were synthesized from trimethylolpropane (TMP) and 2, 2‐dimethylol propionic acid (DMPA) by "quasi‐one‐step method." Then, isophorone diisocyanate (IPDI), polybutylene adipate (CMA‐1044), DMPA and 1, 4‐butanediol (BDO) were utilized to prepare the urethane prepolymer (PU), which was reacted with HBPE to synthesize hyperbranched polyurethanes (HBPU). Finally, 1–3 generations of fluoroalkyl‐end‐capped hyperbranched polyurethanes (FHBPU) latexes were obtained by the reaction of perfluorohexyl ethanol (S104) and HBPU as well as the self‐emulsification process. Structure of the products, the properties of different FHBPU emulsions and its films were investigated by FTIR, 1 H NMR, TEM, DLS, TGA, XPS, XRD, SEM, AFM and static contact angle measuring instrument. Results showed that the particle size of FHBPU latexes increased gradually with the increase of generation number. SEM and XRD results verified that an amount of the crystal particles was increased with the increase of generation number. XPS and AFM demonstrated that degree of microphase separation and film roughness was increased with the increase of branching degree. Static water contact angles could attain 95.9°, 100.3°, and 107.0°, respectively on the 1–3 generations of FHBPU films, compared to that on PU (75.1°). Abstract :